Meningkatkan Pemahaman IPA dengan Model Pembelajaran Problem Based Learning (PBL) pada Siswa Kelas V SDN Kertobanyon - Septyana Dwi Kusuma Wardani; Nurul Kusuma Dewi; Tri Susi Artina Wati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The purpose of this study was to determine the extent to which fifth grade students of SDN Kertobanyon were able to master the science subject "Hearing Because of Sound" with the Problem Based Learning (PBL) learning approach. Using a descriptive qualitative methodology, the process and influence of PBL implementation on student understanding were studied. Direct observation, in-depth student interviews, and document analysis were used to collect data, which were then analyzed using descriptive analysis methods, the form of this research is Classroom Action Research (CAR). The results showed that the implementation of PBL succeeded in significantly increasing student engagement, with students showing improvements in communication skills, group work, and critical thinking. In addition, students said that the PBL paradigm improved their understanding of good ideas and made learning more interesting and participatory. However, this study also identified several challenges, including differences in student ability levels and limited time available for problem solving. To overcome these challenges, teachers are advised to provide additional support to students who need it and develop more efficient learning strategies. In conclusion, the PBL model is effective in improving students' understanding of science and science concepts and can be applied more widely in the context of elementary school learning, as long as it is carried out with careful planning and adaptation to classroom conditions.